Prevalence of work-related musculoskeletal disorders and vision problems among electronics industry employees in Chennai, India - Nelson, Sharon; Saranya R; Naveen Shyam Sundar (International Journal of Occupational Safety and Health, 2026)
Introduction: Employees of the electronics industry are exposed to ergonomic hazards due to repetitive tasks, prolonged standing, awkward posture and sustained near work activities resulting in work related musculoskeletal disorders (WMSD) and vision problems. The presence of these hazards could affect the productivity and well-being of the individual. The study was conducted to estimate the prevalence of WMSDs and vision problems among the employees and to assess factors associated with these occupational health outcomes. Methods: A cross-sectional study was done during December 2024 – January 2025 among 259 employees of an electronics company in Chennai using simple random sampling. A semi-structured questionnaire containing demographic details and work profile, Nordic musculoskeletal questionnaire to assess the prevalence of work-related musculoskeletal disorders and a questionnaire to assess the prevalence of vision problems were used for collecting data. Data was entered in MS excel and analyzed using SPSS version 16. Descriptive statistics were used, and associations were tested using the Chi-square test with odds ratios and 95% confidence intervals. Results: The mean age of the participants was 24.16 ± 4.03 years and 76.1% were women. The prevalence of WMSDs was 61.4% and vision problems were reported by40.2%. The shoulder (52.1%) and neck (49%) were the most commonly affected body regions. Eye strain (49%) was the most frequent visual complaint. WMSDs and vision problems showed significant associations with gender, job process, work shift, work experience, and health-related leave taken (p < 0.05). Conclusion: The study showed a high prevalence of WMSD and vision problems in the electronics workforce. These findings highlight the need for ergonomics risk assessment as well as routine health screening to enable early identification and prevention of these occupational health problems.